2019
DOI: 10.1261/rna.072116.119
|View full text |Cite
|
Sign up to set email alerts
|

Pol5 is an essential ribosome biogenesis factor required for 60S ribosomal subunit maturation in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, more than 250 trans-acting factors are involved in the maturation of 40S and 60S ribosomal subunits. The expression of most of these factors is transcriptionally coregulated to ensure correct ribosome production under a wide variety of environmental and intracellular conditions. Here, we identified the essential nucleolar Pol5 protein as a novel trans-acting factor required for the synthesis of 60S ribosomal subunits. Pol5 weakly and/or transiently associates with early to medium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 99 publications
1
7
0
Order By: Relevance
“…That indicates that the genes have diverse functions (Hogues et al ., 2008; Yu et al ., 2010; Rodríguez-Sánchez et al ., 2011; Mukherjee et al ., 2012; Pattabiraman and Gonda, 2013; Roy, 2016; X. Wang et al ., 2018; Ma and Constabel, 2019; Ramos-Sáenz et al ., 2019), and might not all be traditional transcription factors. The latter is often implied for plant Myb proteins (Wieser and Adams, 1995; Mateos et al ., 2006; Du et al ., 2009; Dubos et al ., 2010; Lin et al ., 2011, 2012; Prouse and Campbell, 2012; Ambawat et al ., 2013; Pattabiraman and Gonda, 2013; Kim et al ., 2014; Baldoni et al ., 2015; Dong et al ., 2015; Liu et al ., 2015; Roy, 2016; Matheis et al ., 2017; Valsecchi et al ., 2017; Verma et al ., 2017; Allan and Espley, 2018; Mitra, 2018; X.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That indicates that the genes have diverse functions (Hogues et al ., 2008; Yu et al ., 2010; Rodríguez-Sánchez et al ., 2011; Mukherjee et al ., 2012; Pattabiraman and Gonda, 2013; Roy, 2016; X. Wang et al ., 2018; Ma and Constabel, 2019; Ramos-Sáenz et al ., 2019), and might not all be traditional transcription factors. The latter is often implied for plant Myb proteins (Wieser and Adams, 1995; Mateos et al ., 2006; Du et al ., 2009; Dubos et al ., 2010; Lin et al ., 2011, 2012; Prouse and Campbell, 2012; Ambawat et al ., 2013; Pattabiraman and Gonda, 2013; Kim et al ., 2014; Baldoni et al ., 2015; Dong et al ., 2015; Liu et al ., 2015; Roy, 2016; Matheis et al ., 2017; Valsecchi et al ., 2017; Verma et al ., 2017; Allan and Espley, 2018; Mitra, 2018; X.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2018;Li et al, 2019Li et al, , 2019Ma and Constabel, 2019;Cao et al, 2020) although proteins that are not classical transcription factors can contain Myb type DNA binding domains (Hogues et al, 2008;Yu et al, 2010;Rodríguez-Sánchez et al, 2011;Mukherjee et al, 2012;Pattabiraman and Gonda, 2013;Roy, 2016;X. Wang et al, 2018;Ma and Constabel, 2019;Ramos-Sáenz et al, 2019). The Myb family does not have many members comprising 4 to 5 proteins in animal genomes (Prouse and Campbell, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Please note that depletion of the small ribosomal subunit biogenesis factor, Pwp2, for 14 h leads to the reduction of small ribosomal subunit pre-and mature rRNAs (20S and 18S rRNA, respectively) [39]. In contrast depletion of the large ribosomal subunit biogenesis factor, Pol5, for 9 h leads to the reduction of the common large ribosomal subunit precursor and corresponding mature rRNA (27S, 25S, and 5.8S, respectively) [39][40][41]. Additional application examples using this protocol and S. cerevisiae is described in [41] 1.…”
Section: Methodsmentioning
confidence: 99%
“…The study of fungal MYB TFs started late, to date they were only reported in the form of single gene in fungi such as yeast, Aspergillus nidulans, Aspergillus fumigatus and Magnaporthe oryzae. Preliminary studies have found that they are essential for fungal spore formation and fungal pathogenicity to plant (Arratia-Quijada et al, 2012;Dong et al, 2018;Sarikaya Bayram et al, 2018;Ramos-Sáenz et al, 2019).…”
mentioning
confidence: 99%